Changes in behavior are unable to disrupt a trophic cascade involving a specialist herbivore and its food plant. Issue 9 (8th April 2019) - Lohman, Madeleine G.; Riecke, Thomas V.; Acevedo, Cheyenne R.; Person, Brian T.; Schmutz, Joel A.; Uher‐Koch, Brian D.; Sedinger, James S.
Abstract: Changes in ecological conditions can induce changes in behavior and demography of wild organisms, which in turn may influence population dynamics. Black brant ( Branta bernicla nigricans ) nesting in colonies on the Yukon–Kuskokwim Delta (YKD) in western Alaska have declined substantially (~50%) since the turn of the century. Black brant are herbivores that rely heavily on Carex subspathacea (Hoppner's sedge) during growth and development. The availability of C. subspathacea affects gosling growth rates, which subsequently affect pre‐ and postfledging survival, as well as size and breeding probability as an adult. We predicted that long‐term declines in C. subspathacea have affected gosling growth rates, despite the potential of behavior to buffer changes in food availability during brood rearing. We used Bayesian hierarchical mixed‐effects models to examine long‐term (1987–2015) shifts in brant behavior during brood rearing, forage availability, and gosling growth rates at the Tutakoke River colony. We showed that locomotion behaviors have increased ( β  = 0.05, 95% CRI: 0.032–0.068) while resting behaviors have decreased ( β  = −0.024, 95% CRI: −0.041 to −0.007), potentially in response to long‐term shifts in forage availability and brood density. Concurrently, gosling growth rates have decreased substantially ( β  = −0.100, 95% CRI: −0.191 to −0.016) despite shifts in behavior, mirroring long‐term declines in the abundance of C. subspathacea ( β  = −0.191, 95% CRI: −0.355 to −0.032). These results have important implications for individual fitness and population viability, where shifts in gosling behavior putatively fail to mitigate long‐term declines in forage availability. Abstract : Changes in ecological conditions can induce changes in behavior and demography of wild organisms, which in turn may influence population dynamics. Black brant ( Brant bernicla nigricans ) gosling growth rates have decreased substantially ( β  = −0.100, 95% CRI: −0.191 to −0.016) in response to long‐term declines in the abundance of C. subspathacea ( β  = −0.191, 95% CRI: −0.355 to −0.032), despite shifts in locomotion ( β  = 0.05, 95% CRI: 0.032–0.068) and resting ( β  = −0.024, 95% CRI: −0.041 to −0.007) behaviors. These results have important implications for individual fitness and population viability, where shifts in gosling behavior putatively fail to mitigate long‐term declines in forage availability.